(untitled) (Élisée - Revista de Geografia da UEG, 2025)
Water resources are vital for economic development and quality of life, but they face challenges due to urban expansion and improper land use. The study, using MapBiomas data and conducting a reclassification according to research requirements, analyzed land use from 1992 to 2022 in the municipalities of Corumbaíba, Caldas Novas, and Ipameri. The maps were created from MapBiomas Collection 8 data and processed in ArcGIS. The results were reclassified into five main categories. There was a significant reduction in forested area and a substantial increase in agriculture and urban expansion. The research highlights the importance of understanding and sustainably using land in the region of the Corumbá Hydroelectric Power Plant, emphasizing the effectiveness of MapBiomas in land use analysis. It also emphasizes the need for measures to ensure the sustainability of water resources for future generations.